2006
DOI: 10.1021/np0503451
|View full text |Cite
|
Sign up to set email alerts
|

1-Deoxypaclitaxel and abeo-Taxoids from the Seeds of Taxus mairei

Abstract: A new paclitaxel derivative and two new 2(3-->20)-abeo-taxoids were isolated from a methanol extract of the seeds of Taxus mairei, and their structures were established as 1-deoxypaclitaxel (1), 7beta,10beta-diacetoxy-2alpha,5alpha,13alpha-trihydroxy-2(3-->20)-abeo-taxa-4(20),11-dien-9-one (2), and 2alpha,13alpha-diacetoxy-10beta-hydroxy-2(3-->20)-abeo-taxa-4(20),6,11-triene-5,9-dione (3) on the basis of spectroscopic data analysis. Taxane 1 is the first example of a paclitaxel analogue with a C-1beta hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Compared to 4-6 and 16, the introduction of an O-b-xylose in R 2 (7)(8)(9)(10)(11) or loss of the C-13 ester side chain (14-15) greatly decrease their activities, which is consistent with the reported SAR of taxol analogues. 27 Interestingly, despite of the general low activity, the O-b-xylose bearing compounds 7-11 reserved their anti-proliferative activity and showed selective cytotoxicity towards certain cancer cell lines.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Compared to 4-6 and 16, the introduction of an O-b-xylose in R 2 (7)(8)(9)(10)(11) or loss of the C-13 ester side chain (14-15) greatly decrease their activities, which is consistent with the reported SAR of taxol analogues. 27 Interestingly, despite of the general low activity, the O-b-xylose bearing compounds 7-11 reserved their anti-proliferative activity and showed selective cytotoxicity towards certain cancer cell lines.…”
supporting
confidence: 80%
“…8 Previous phytochemical studies on this plant have led to the isolation a number of taxanes, some of which showed significant cytotoxicity. [9][10][11][12][13][14] In our screening program aimed at the discovery of structurally unique and biologically significant taxanes from Taxus plants, a new taxane glucoside, 7b,9a,10b-triacetoxy-13a-hydroxy-5a-O-(b-D-glucopyranosyl) taxa-4(20),11-diene (1), and 14 known analogues ( Fig. 1), 2-deacetoxytaxinine J 15 (2), 2-deacetoxyaustrospicatine 16 (3), cephalomannine 17 (4), 10-deacetyl-7-epi-taxol 18 (5), taxol 19 (6), 7-xylosyl-10-deacetyl taxol 20 (7), 7-b-xylosyl-cephalomannine 20 (8), 7-b-xylosyl-taxol 20 (9), 7-b-xylosyl-10-deacetyl-cephalomannine 20 (10), 7-xylosyl-10-deacetyl taxol C 20 (11), taxinine M 21 (12), taxacin 22 (13), 10-deacetylbaccatin III 23 (14), and baccatin III 17,20 (15) were isolated from the barks of T. wallichiana var.…”
mentioning
confidence: 99%
“…We are now isolating other diterpenoids from various plants, particularly from Taxus mairei (33), and searching for novel diterpenoids that have greater anti-proliferative activity in human cancer cells than kayadiol.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Most of modification and study of SAR of taxoids were focused on paclitaxel and its analogs with 6/8/6 skeleton and an oxetane ring. 1)-abeo-taxoids with 5/7/6 skeleton.…”
Section: Introductionmentioning
confidence: 99%